Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.4161/cib.21554
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer drug discovery and development

Abstract: Deregulated apoptosis is a hallmark of cancer, and the B-cell lymphoma-2 (Bcl-2) family of proteins is pivotal to mediating the intrinsic pathway of this process. Recent advances have yielded both pan-Bcl-2 small molecule inhibitors (SMIs) that inhibit both the Bcl-2 and the Mcl-1 arm of the Bcl-2 family anti-apoptotic proteins, as well as selective SMIs to differentially target the two arms. Of these SMIs, ABT-263 (navitoclax), AT-101 [(-)-gossypol], and obatoclax (GX15-070) are currently in clinical trials f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 129 publications
0
22
0
Order By: Relevance
“…Next, we studied the mechanism behind the EWS-FLI1 dependent differential response to the tested BCL-2 family inhibitors. Although the target profiles of obatoclax and navitoclax were similar, affinities and the selectivity for the anti-apoptotic BCL-2 family members differed dramatically [ 22 ]. Navitoclax, like ABT-737, shows strong affinity for BCL-2, BCL-X(L), and BCL-W, while they are inactive towards MCL-1 and BCL-B.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we studied the mechanism behind the EWS-FLI1 dependent differential response to the tested BCL-2 family inhibitors. Although the target profiles of obatoclax and navitoclax were similar, affinities and the selectivity for the anti-apoptotic BCL-2 family members differed dramatically [ 22 ]. Navitoclax, like ABT-737, shows strong affinity for BCL-2, BCL-X(L), and BCL-W, while they are inactive towards MCL-1 and BCL-B.…”
Section: Resultsmentioning
confidence: 99%
“…The BCl-2 homology 3 (BH3) protein preferentially binds to BCl-2 through its homology domain and neutralizes its activity to induce apoptosis (66, 67). Small molecules mimicking the topology of BH3, referred as BH3 mimics, can bind and deactivate the function of pro-apoptotic BCl-2 and serve as promising drug candidates (68–70). BH3 mimetic small molecules, ABT-737, ABT-263, gossypol, AT-101, and alpha-tocopheryl succinate ( α -TOS) along with other chemotherapeutics, show promising selectivity in targeting pro-apoptotic proteins and increased efficacy (71, 72).…”
Section: Mitochondrial Targets For Cancermentioning
confidence: 99%
“…12 Previous investigators have shown that tumors cannot expand greater than 1-2mm in size without the induction of angiogenesis. 13 Three of the primary activators of angiogenesis which promote endothelial proliferation are vascular endothelial growth factor (VEGF), CXCL1 (growth-related oncogene, GRO-alpha), and CXCL8 (interleukin-8). 13,14 The expression of CXCL8 is activated by the NF-kappaB signaling pathway which is controlled by a pro-angiogenic signaling molecule, Bcl-2.…”
Section: Discussionmentioning
confidence: 99%
“…13 Three of the primary activators of angiogenesis which promote endothelial proliferation are vascular endothelial growth factor (VEGF), CXCL1 (growth-related oncogene, GRO-alpha), and CXCL8 (interleukin-8). 13,14 The expression of CXCL8 is activated by the NF-kappaB signaling pathway which is controlled by a pro-angiogenic signaling molecule, Bcl-2. 16 Recent studies have shown that Bcl-2 is substantially upregulated in HNSCC compared to normal oral mucosal endothelial cells, which would suggest that that HNSCC may have elevated levels of CXCL8.…”
Section: Discussionmentioning
confidence: 99%